Assessment of Risk Factors of Upper Extremity Musculoskeletal Disorders (UEMSDS) by OCRA Method in Repetitive Tasks - SA Moussavi Najarkola (Tehran University of Medical Sciences, 2006)
The high occurrence of upper extremity musculoskeletal disorders (UEMSDS) in Iranian ironwork industries indicates a need to assess the risk factors of the disorders at such workplaces. In order to prevent such disorders, the Occupational Repetitive Actions (OCRA) carried out to obtain an integrated assessment of the various risk factors, classify different jobs and suggest ergonomic designing solutions. Four data gathering methods including Observational, Interview, Nordic Musculoskeletal Questionnaire (NMQ), and OCRA were utilized. All 385 male workers occupying in five various jabs (72 tasks) in Qaemshahre ironwork industry located in the north of Iran were studied. The percent of work tasks lain in low, moderate, and high-risk level were 6.14%, 69.27%, and 24.59%, respectively. Mean of exposure indices between five jobs including administrative (0.69), lathing (2.87), welding (3.43), melting (3.58) and foundry (5.96) jobs showed significant difference (F= 4.881, P= 0.003). In addition, the foundry job had the highest risk of occurrence of UEMSDS. The highest incidence of distal upper extremity was allocated to the hand and fingers region. There was a significant relationship between surveyed work groups and incidences of upper extremities (χ2= 6.425, P= 0.008). The OCRA Method could be a useful method for evaluating risk factors of UEMSDS in repetitive tasks of the ironwork industry.